THE OPEN EDUCATION SYSTEM: FORMATION AND FUNCTIONING - Julia A. Mamonova (Obrazovanie i Nauka)
The study is aimed at developing the basic principles of foundation and functioning of the open educational system, its relevance results from the strategic goal of knowledge integration facing the modern universities.The research findings and novelty: The author identifies the general needs of the users of open educational resources and proves the advantages of organizing the institutional repositories, based on sociological surveys targeting the university students of Nizhny Novgorod and academic staff of several Russian higher schools. The basic principles of the unified educational information and communications environment were developed, and a feasible structure of educational portal presented.The practical significance: The research outcomes, complying with the new ≪consumer strategies≫, can be used by the higher educational institutions for developing the distance system of education and implementing the open educational resources in academic process.